Mobile Platform for Building Applications at the Integrated Services Office Medan City - Astuti, Andriani Dwi; Fakhriza, M.; Harahap, Aninda Muliani (Journal of Computer Networks, Architecture and High Performance Computing, 2024)
The advancement of computer technology has developed rapidly and has been applied in various aspects of life. At that time, computers were considered one of the most efficient tools in supporting technological development. At the Office of Investment and One-Stop Integrated Services (OI-OIS) in Medan City, the process of applying for Building Permits (BP) was still conducted manually and had not been computerized, resulting in slow and inefficient licensing processes. Applicants were required to fill out forms manually and deliver physical documents to the village and sub-district offices, which extended processing times. Furthermore, application reports were often piled up, hindering prompt and accurate handling. The lack of efficiency in managing applicant data further exacerbated the situation and slowed down the completion of applications. Therefore, an integrated digital system was needed to expedite and facilitate the submission and management of IMB applications. This research aimed to develop an Android-based Information System for Building Permit Applications at DPMPTSP in Medan City using the R&D (Research and Development) method. It was hoped that this application would make it easier for staff to manage IMB application data. The research results indicated that the development of the Android-based Information System for Building Permit Applications successfully addressed the issues encountered in the previously manual IMB application process. This application expedited and simplified the filling out and submission of applications, eliminating the need for applicants to deliver physical documents. Additionally, the management of applicant data became more efficient and computerized, reducing the backlog of reports and speeding up the verification process.